2019
DOI: 10.1007/s13139-019-00588-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Applications of Technetium-99m Quantitative Single-Photon Emission Computed Tomography/Computed Tomography

Abstract: Single-photon emission computed tomography/computed tomography (SPECT/CT) is an already established nuclear imaging modality. Co-registration of functional information (SPECT) with anatomical images (CT) paved the way to the wider application of SPECT. Recent advancements in quantitative SPECT/CT have made it possible to incorporate quantitative parameters, such as standardized uptake value (SUV) or %injected dose (%ID), in gamma camera imaging. This is indeed a paradigm shift in gamma camera imaging from qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Accurate absorbed radiation dose estimation at voxel and organ level is only possible with quantitively accurate SPECT data that is corrected for attenuation, scatter, and collimator-detector response. In addition, the use of quantitative SPECT for diagnostic purposes is increasing [233]. However, the SPECT/CT that allows accurate SPECT quantification is not widely available yet.…”
Section: Deep Learning: Future Directionmentioning
confidence: 99%
“…Accurate absorbed radiation dose estimation at voxel and organ level is only possible with quantitively accurate SPECT data that is corrected for attenuation, scatter, and collimator-detector response. In addition, the use of quantitative SPECT for diagnostic purposes is increasing [233]. However, the SPECT/CT that allows accurate SPECT quantification is not widely available yet.…”
Section: Deep Learning: Future Directionmentioning
confidence: 99%
“…First, it is an accurate quantitative tool for evaluating salivary gland function. The statement is based on the recent progress in quantitative SPECT/CT technique 22 , which has been proven in a variety of clinical applications 13 21 . Notably, the current SPECT/CT protocol produced normal %ID (0.36 ± 0.02% for the parotid and 0.17 ± 0.01% for the submandibular) and %EF (61.41 ± 1.38% for the parotid and 45.22 ± 2.46% for submandibular) 12 reference ranges, which are comparable to the results obtained from conventional planar imaging 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent technological development has allowed the application of quantitative nuclear imaging parameters, such as %injected dose (%ID) and standardized uptake value (SUV), to SPECT/CT imaging 13 21 . Quantitative salivary gland SPECT/CT holds promise as a new imaging modality 12 , 22 since the interpretation of the salivary gland scintigraphy depends on the quantitation of the uptake (i.e., %ID) of Tc-99m pertechnetate by the salivary glands. However, some issues remain to be solved before salivary gland SPECT/CT can be widely applied.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently revealed that quantitative single-photon emission computed tomography/computed tomography (SPECT/CT) is more accurate than the traditional thyroid uptake system 19 . In addition, the quantitative SPECT/CT scan can discriminate patients with destructive thyroiditis from euthyroid patients and is expected to play a critical role in differentiating thyroid disease in the future 22,23 . Nevertheless, many strengths have been stated with SPECT/CT scan, and traditional planar scintigraphy still plays an important role in the differential diagnosis of thyrotoxicosis patients, including delineations of hot nodules 19 .…”
Section: Discussionmentioning
confidence: 99%